Students' Strategies in Mastering English Vocabulary: A Descriptive Qualitative Study at SDI NW Anak Dui, Kesik - Maryam, Baiq; Nazri, M. Adib; Husnu, M. (Lembaga Bale Literasi, 2026)
This study aims to identify the strategies used by students at SDI NW Anak Dui, Kesik, in mastering English vocabulary, and to explore the factors that influence their selection of these strategies. The research employed a descriptive qualitative method, chosen to gain an in-depth understanding of the vocabulary learning behaviors of elementary school learners within their natural classroom setting. Data were collected through a structured multiple-choice questionnaire consisting of twelve items, distributed to twenty students who were selected through purposive sampling during the second semester of the 2024/2025 academic year. The data were analyzed using frequency distribution and presented in percentages, then interpreted descriptively through the lens of vocabulary learning strategy (VLS) theory. The findings reveal that students at SDI NW Anak Dui employ a diverse range of vocabulary learning strategies. Twenty-five percent rely on reading books, articles, or newspapers; twenty-five percent prefer auditory media such as music and podcasts; twenty percent watch English films and television programs; twenty percent use flashcards; while five percent practice with peers and another five percent infer meaning from context. The selection of strategies is shaped by personal learning style (40%), teacher recommendations (20%), availability of learning resources (20%), time availability (10%), and vocabulary difficulty (10%). Motivation, teacher guidance, and peer influence emerged as significant social-affective factors. The study highlights the importance of designing multimodal vocabulary instruction tailored to learners' cognitive preferences and contextual conditions at the elementary level.